Benthic-pelagic trophic coupling in an Arctic marine food web along vertical water mass and organic matter gradients - Stasko, Ashley D; Bluhm, Bodil; Michel, Christine; Archambault, Philippe; Majewski, Andrew; Reist, James D; Swanson, Heidi; Power, Michael (Marine Ecology Progress Series, 2018)
Source at: http://doi.org/10.3354/meps12582 Understanding drivers of benthic-pelagic coupling in Arctic marine ecosystems is key to identifying benthic areas that may be sensitive to climate-driven changes in hydrography and surface production. We coupled algal biomass and sedimentary characteristics with stable isotope data for 113 fishes and invertebrates in the Canadian Beaufort Sea and Amundsen Gulf to examine how trophic structure was influenced by the vertical water mass structure and organic matter input regimes, from 20 to 1000 m depths. Indices of community-level trophic diversity (isotopic niche size, 13C enrichment relative to a pelagic baseline, and δ13C isotopic range) increased from west to east, coincident with the use of more diverse dietary carbon sources among benthic functional groups. Data suggested benthic-pelagic trophic coupling was strongest in the western study region where pelagic sinking flux is relatively high, intermediate in the central region dominated by riverine inputs of terrestrial organic matter, and weakest in the east where strong pelagic grazing is known to limit sinking flux. Differences in δ13C between pelagic and benthic functional groups (up to 5.7 ‰) increased from west to east, and from the nearshore shelf to the upper slope. On the upper slope, much of the sinking organic matter may be intercepted in the water column, and dynamic hydrography likely diversifies available food sources. In waters > 750 m, there were no clear trends in benthic-pelagic coupling or community-level trophic diversity. This study represents the first description of fish and invertebrate food web structure > 200 m in the Canadian Beaufort Sea.